Report on industrial attachment with Agilis Communication Technologies Singapore (Pte) Ltd - Soon, Chen Peng. (2008)
Study on the local oscillator controller board was carried out to analyse and document the hardware functionality. Modifications were made for the existing calibration software, which corrects for the drift of the DTO over time.